Energy Cost of Slow and Normal Gait Speeds in Low and Normally Functioning Adults. (November 2019) - Rowley, Taylor W.; Cho, Chi; Swartz, Ann M.; Staudenmayer, John; Hyngstrom, Allison; Keenan, Kevin G.; Welch, Whitney A.; Strath, Scott J.
Abstract : Objective: Slow walking speed paired with increased energy cost is a strong predictor for mortality and disability in older adults but has yet to be examined in a heterogeneous sample (ie, age, sex, disease status). The aim of this study was to examine energy cost of slow and normal walking speeds among low- and normal-functioning adults. Design: Adults aged 20–90 yrs were recruited for this study. Participants completed a 10-m functional walk test at a self-selected normal walking speed and were categorized as low functioning or normal functioning based on expected age- and sex-adjusted average gait speed. Participants completed two successive 3-min walking stages, at slower than normal and normal walking speeds, respectively. Gas exchange was measured and energy cost per meter (milliliter per kilogram per meter) was calculated for both walking speeds. Results: Energy cost per meter was higher ( P < 0.0001) in the low-functioning group ( n = 76; female = 59.21%; mean ± SD age = 61.13 ± 14.68 yrs) during the slower than normal and normal ( P < 0.0001) walking speed bouts compared with the normal-functioning group ( n = 42; female = 54.76%; mean ± SD age = 51.55 ± 19.51 yrs). Conclusions: Low-functioning adults rely on greater energy cost per meter of walking at slower and normal speeds. This has implications for total daily energy expenditure in low-functioning, adult populations.